2013, Nr. 13, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting and auditing challenges Jonas Mackevičius, Jonas Martinavičius, Lionius Gaižauskas, The analysis of accounting and audit specialists release and their satisfaction with studies at Vilnius University (1990-2012), 7 Dovilė Latakaitė, Kristina Rudžionienė, Corporate social responsibility information disclosure in the financial reports, 21 Lukas Giriūnas, Evaluation of the determinants of fraud and errors, 32 Светлана Бычкова, Елeна Итыгилова, Institutional substantiation of the concept of responsibility in auditing: philosophical, sociological and economic aspects, 40 Lionius Gaižauskas, Jonas Martinavičius, Budgetary control challenges in Lithuanian companies, 50 Problems of financial markets and economics Inese Vigante, Ruta Sneidere, Problematic aspects of the VAT Reverse charge arrangements, 63 Arvydas Paškevičius, Clients of equity-index lined bonds: risk assessment, 79 Valentina Bogatyrova, The efficiency increase problems in the Belarussian economy: financial management of human capital, 96 Marija Kučinskienė, Dainius Baliūnas, Environment influence assessment to inflections of structural changes, 109 Elena Kurlavičiūtė, The comparative analysis of Lithuanian and Finland expenditure on public goods, 117